FANCA Gene Mutations in North African Fanconi Anemia Patients - Ben Haj Ali, Abir (Front Genet, 2021)
Populations in North Africa (NA) are characterized by a high rate of consanguinity. Consequently, the proportion of founder mutations might be higher than expected and could be a major cause for the high prevalence of recessive genetic disorders like Fanconi anemia (FA). We report clinical, cytogenetic, and molecular characterization of FANCA in 29 North African FA patients from Tunisia, Libya, and Algeria. Cytogenetic tests revealed high rates of spontaneous chromosome breakages for all patients except two of them. FANCA molecular analysis was performed using three different molecular approaches which allowed us to identify causal mutations as homozygous or compound heterozygous forms. It included a nonsense mutation (c.2749C > T; p.Arg917Ter), one reported missense mutation (c.1304G > A; p.Arg435His), a novel missense variant (c.1258G > A; p.Asp409Glu), and the FANCA most common reported mutation (c.3788_3790delTCT; p.Phe1263del). Furthermore, three founder mutations were identified in 86.7% of the 22 Tunisian patients: (1) a deletion of exon 15, in 36.4% patients (8/22); (2), a deletion of exons 4 and 5 in 23% (5/22) and (3) an intronic mutation c.2222 + 166G > A, in 27.3% (6/22). Despite the relatively small number of patients studied, our results depict the mutational landscape of FA among NA populations and it should be taken into consideration for appropriate genetic counseling.